Pengaruh Nilai Tukar dan Inflasi terhadap Financial Distress - Judijanto, Loso; Antari, Ni Luh Sili; Yakup, Anggita Permata; Raraga, Filus; Sesario, Revi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This research aims to analyze the effect of ROA, interest rates, inflation and exchange rates on financial distress in financial sector companies listed on the IDX for the 2019-2023 period. This research uses a quantitative method with regression analysis. The data source is from secondary data in the form of financial reports of financial sector companies listed on the IDX, through the official website of the Indonesia Stock Exchange (IDX), namely (www.idx.co.id) for the 2019-2023 period. Determination of the sample was determined using the purposive sampling method. Purposive sampling is a research sampling technique by fulfilling certain elements. From the criteria that have been set, this study obtained a sample of 53 companies with a total sample for 5 observation periods totaling 265 samples. After all the data was obtained, it was then analyzed using the IBM SPSS statistics software program version 26, namely using the multiple linear regression analysis method. The results of the study showed that the exchange rate and inflation did not affect financial distress in financial sector companies listed on the IDX for the 2019-2023 period.